Prevalence and factors associated with hearing impairment among workers working in power stations in Sarawak - Mohd Nizam J,; Khiew S.K.,; Noor Hassim I., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
A cross-sectional study of hearing impairment due to occupational noise exposure was conducted among 261 workers working in power statiom in Sarawak for the year 2003. The purpose of this study was to determine the prevalence of hearing impairment among these workers and factors associated with it. The study was conducted by using available annual audiometric data done in 2003. The result of this study revealed that the prevalence of hearing impairment was 55.9%. Age, duration of employment and types of electricity generator used in the power stations were factors found to be signijicantly associated with hearing impairment. The water-turbine generator which was found in hydroelectric power station produced less noise and had resulted in lower prevalence of hearing impairment (39.4%) when compared with that of the gas-turbine type (58.3%) which was found in power station using diesel and natural gas (Chisquare= 4.195, p < 0.05). Through logistic regression analysis, variable that had significantly contributed to the hearing impairment was the duration of employment. It is concluded that the high prevalence of hearing loss among these workers is a cause of deep concern. The findings of this study highlighted the magnitude of the problem, the necessity of the application of aggressive hearing conservation program and the need for more studies in this field.